Effect of feeding a low lactose yogurt-based diet having galactooligosaccharides (GOS) on bone health: preclinical model of normal growth - Seijo, Mariana (2021)
GOS are natural prebiotics of human milk that could have positive actions in calcium (Ca) absorption and bone health. They can be incorporated in fermented dairy products by enzymatic action on milk lactose, resulting in a low lactose-containing food. We evaluated and compared the effect of feeding a low lactose-yogurt containing GOS (EY) in bone health during normal growth of weaning rats. Rats (n=10/group) fed 3 diets: control AIN´93-G (C); GOS-free yogurt (Y) or EY during 30 days. We evaluated food consumption; body weight (BW); Ca absorption (% AbsCa) by balance methods; in cecum Lactobacilli growth (LB) by microbiological culture, pH by a pHmeter and short chain fatty acids (SCFA) by HPLC-IR; total skeleton (Et), lumbar spine (Ls) and proximal tibia (Pt) bone mineral density (BMD) and Et bone mineral content (BMC) by densitometry; bone volume (%BV) and intestinal crypt depth (ICD) (µm) by histology; maximal load, fracture strength and elastic modulus by biomechanical test. ANOVA and Bonferroni post hoc test were used to evaluate statistical significances. Food consumption and BW were similar thought out the study. EY showed higher %AbsCa (p<0.05), LB colonies (p<0.05); SCFA concentration (p<0.001) and lower cecal pH (p<0.01) than Y and C. EY had the highest Ls and PtBMDs (p<0.05), %BV (p<0.01), ICD (p<0.0001) than YC and C without differences in EtBMC vs C. EY had higher biomechanical parameters than Y (p<0.01) without differences vs. C. Conclusion: YE could be a useful tool to ensure an optimal bone growth in lactose intolerance conditions.